Virtues of volatility: a facile transesterification approach to boronic acids - Hinkes, Stefan; Klein, Christian D. (Organic letters, 2019)
Boronic acids are an increasingly important compound class for many applications, including C-C bond formation reactions, medicinal chemistry, and diagnostics. The deprotection of boronic ester intermediates is frequently a problematic and inefficient step in boronic acid syntheses. We describe an approach that highly facilitates this transformation by leveraging the volatility of methylboronic acid and its diol esters. The method is performed under mild conditions, provides high yields, and eliminates cumbersome and problematic purification steps.